2009
DOI: 10.1063/1.3056603
|View full text |Cite
|
Sign up to set email alerts
|

Polarization fatigue in ferroelectric thin films and related materials

Abstract: The experimental characteristics of polarization fatigue in thin-film, bulk ceramic, and single-crystalline ferroelectrics have been reviewed in detail. Various scenarios and models proposed for fatigue in ferroelectric materials during the past few decades have been discussed, together with our own model developed very recently [Phys. Rev. Lett. 97, 177601 (2006); Phys. Rev. B 75, 244104 (2007)]. Interpretations for the experimental data reviewed in this paper but untreated in our previous work [Phys. Rev. B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
222
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(234 citation statements)
references
References 195 publications
9
222
0
3
Order By: Relevance
“…The fatigue phenomenon for PZT thin film is especially pronounced with metal electrodes such as Pt. Different fatigue models and mechanisms have been reviewed by Tangantsev et al [9] and Lou et al [10]. Accumulation of oxygen vacancies at the ferroelectric/electrode interface and/or injection of charge carriers through the interface have been suggested to be related to the fatigue phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…The fatigue phenomenon for PZT thin film is especially pronounced with metal electrodes such as Pt. Different fatigue models and mechanisms have been reviewed by Tangantsev et al [9] and Lou et al [10]. Accumulation of oxygen vacancies at the ferroelectric/electrode interface and/or injection of charge carriers through the interface have been suggested to be related to the fatigue phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…Systematic loss of the switchable polarization under cyclic external field is known as polarization fatigue. [6][7][8] Several mechanisms have been proposed in literature for explaining the fatigue behavior of a ferroelectric material including accumulation of charged defects at domain walls leading to their pinning, 9 formation of space charge layer at ferroelectric-electrode interface, 10,11 formation of micro-cracks due to residual strain, 12,13 field-driven phase transition, 14 and field-driven diffusion of electrode metal to grain boundaries. 15 Depending upon the operating conditions (temperature, external field magnitude, and frequency) and microstructure of the material, one or more of these fatigue mechanisms can play the governing role.…”
mentioning
confidence: 99%
“…15 Depending upon the operating conditions (temperature, external field magnitude, and frequency) and microstructure of the material, one or more of these fatigue mechanisms can play the governing role. 7 In bulk polycrystalline ceramics, fatigue is highly dependent on the surface, interface, and grain boundary related imperfections. 7 In single crystals, the fatigue is mainly dominated by the accumulation of charged defects at domain boundaries and formation of micro-cracks due to the residual hysteretic strain.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…oxygen vacancies, redistribution 10-14 and local phase decomposition. [15][16][17] In our previous report, we have demonstrated that charge injection is likely the cause of fatigue in BiFeO 3 . 18 By using a planar capacitor (inset of Fig.…”
mentioning
confidence: 99%